Samoa : Financial Sector Assessment Program. (IMF Staff Country Reports; Country Report, 2015)
EXECUTIVE SUMMARY AND KEY RECOMMENDATIONS The Samoan financial sector is dominated by commercial banks and Public Financial Institutions (PFIs). The four commercial banks provide almost 60 percent of credit to the economy, and the most important PFIs, the Samoa National Provident Fund, and the Development Bank of Samoa, account for around 30 percent. There is also a small and shrinking offshore banking sector without linkages to the domestic financial sector. Banks are liquid and report high capitalization, but close supervisory attention is required in light of high and rising non-performing loans (NPLs) and the results of the FSAP stress tests.1 Banks are still dealing with the effects from past natural disasters, and assessments of their health are impeded by the significant uncertainty surrounding the quality of balance sheet data, in particular on asset quality and provisioning. High loan concentration and exposure to natural disasters represent significant risks to the financial system. The stress tests illustrate that the local banks are relatively less resilient and could not withstand a severely adverse scenario. Thus, close monitoring, through on-site supervision and asset quality reviews, paired with prompt corrective action and a plan to address NPLs (including in PFIs) as needed, are top priorities. PFIs are particularly vulnerable to shocks due to low asset quality and strong linkages with state owned enterprises. This is largely the result of increased policy lending in response to the extraordinary economic stress from recent natural disasters. Significant stress in PFIs could have significant impact on other financial institutions (FIs) through the effect on the economy, and explicit and implicit government guarantees raise potential fiscal risks. The authorities, therefore, are encouraged to step up oversight of the PFIs, including through enhanced data collection and on-site reviews. Where substantial adjustments are needed, new lending should be restricted. The Central Bank of Samoa (CBS), as the main supervisor and regulator of domestic financial institutions, has made important efforts to strengthen its oversight in recent years. These efforts include conducting on-site inspections, introducing elements of risk-based supervision, expanding staff resources, initiating PFI supervision, submission of a new CBS Act (CBA) to reform governance and safeguards, promoting financial inclusion, and progress on Anti-Money Laundering and Combating Financing of Terrorism (AML/CFT). Still, much remains to be done, including improving the quality and coverage of the financial sector data, upgrading legal, regulatory and supervisory frameworks, and building capacity and staff.